Значення супресії функції яєчників у лікуванні хворих на рак молочної залози у пременопаузі - Щепотін, І. Б.; Зотов, О. С.; Любота, Р. В.; Любота, І. І. (Clinical Endocrinology and Endocrine Surgery, 2013)
Hormone therapy is the oldest method of systemic treatment of patients with breast cancer. There are several methods of ovarian ablation: surgery, medication or radiation castration. Currently, there are no clinical studies that aim to compare the effectiveness of different methods of ovarian ablation, so considered that different methods of ovarian ablation are equally effective. In this review included 10 randomized trials involving 11135 patients, which examined the effectiveness of the ovarian ablation in premenopausal women with breast cancer. The results of these studies allow to optimized the use of ovarian ablation in patients with breast cancer.